2021
DOI: 10.1371/journal.pone.0248523
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping pattern and activities of daily living modulate protein expression in AMD

Abstract: Degeneration of macular photoreceptors is a prominent characteristic of age-related macular degeneration (AMD) which leads to devastating and irreversible vision loss in the elderly population. In this exploratory study, the contribution of environmental factors on the progression of AMD pathology by probing the expression of candidate proteins was analyzed. Four hundred and sixty four participants were recruited in the study comprising of AMD (n = 277) and controls (n = 187). Genetics related data was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…It has been observed that sleeping is not only associated with many systemic diseases, such as hypertension ( Levenson et al, 2017 ) and coronary heart disease ( Cheng et al, 2014 ; Lao et al, 2018 ), but also with eye diseases, such as diabetic retinopathy ( Tan et al, 2018 ), vision impairment ( Sun et al, 2021 ), dry eye ( Au et al, 2019 ; Zheng et al, 2022 ), myopia and cataract ( Zhou et al, 2023 ). Interestingly, researchers provided evidence that night sleeping hours were associated with the decreased expression of TIMP-3, IER3, and SLC16A8 in AMD patients ( Sharma et al, 2021 ). In addition disrupted sleep patterns also promote AMD due to the production of reactive oxygen species, a lack of oxygen and inflammatory markers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) ( Colak et al, 2012 ; Irwin, 2019 ; Han et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that sleeping is not only associated with many systemic diseases, such as hypertension ( Levenson et al, 2017 ) and coronary heart disease ( Cheng et al, 2014 ; Lao et al, 2018 ), but also with eye diseases, such as diabetic retinopathy ( Tan et al, 2018 ), vision impairment ( Sun et al, 2021 ), dry eye ( Au et al, 2019 ; Zheng et al, 2022 ), myopia and cataract ( Zhou et al, 2023 ). Interestingly, researchers provided evidence that night sleeping hours were associated with the decreased expression of TIMP-3, IER3, and SLC16A8 in AMD patients ( Sharma et al, 2021 ). In addition disrupted sleep patterns also promote AMD due to the production of reactive oxygen species, a lack of oxygen and inflammatory markers, such as C-reactive protein (CRP) and interleukin-6 (IL-6) ( Colak et al, 2012 ; Irwin, 2019 ; Han et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Daily life activities like sleeping patterns are also known to modulate the protein expression of the genes. 15 We have also identified that genetic variants and subsequent protein alterations especially lipid metabolising proteins (APOE and LIPC) can modulate the anti-VEGF response in wet AMD patients. 53 But, the translation of such studies to diagnostic and therapeutic advancement remains neglected because most of the studies lack the approach to consider the clinical findings, genotype, protein expression and socio-demographic variables as an integral entity to dissect the AMD complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the association of AMD with various genetic factors. Genetic variants of complement factors (C2, CFI, CFH, CCL2), angiogenesis (VEGFs, VEGFRs, etc), pro-angiogenic genes (TIMP3, ADAMTS9), and metabolizing genes (LIPC, APOE) genes have been reported to be associated with the risk of AMD 15–20 genetic polymorphisms in different genes have been linked to AMD like CFHY402H (rs1061170), ARMS2 (rs10490924), C2 (rs547154), ABCA1 (rs1883025), VEGFA (rs4711751) are associated with advanced AMD, ie, neovascular form of AMD, 21 genetic polymorphisms in TLR are associated with AMD in Indian population. 19 Some studies have shown a negative association of AMD with genetic variants of rs2075650 ofApoE, 22 rs10468017 of hepatic lipase (LIPC), 23 and allele T of variant rs493258of hepatic lipase.…”
Section: Introductionmentioning
confidence: 99%